Integrasi Tradisi dan Modernitas dalam Reformasi Pendidikan Pesantren: Studi Kasus Kawasan Pesantren Sidosermo Surabaya - Kurniadi, Kurniadi; Mu’aziz, Farchan; Muslicha, Aruni Ratna (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2025)
Pesantren plays an important role in Islamic education in Indonesia. However, in the modern era, pesantren face challenges in adapting traditional values ​​with formal education and modern technology. This study aims to examine the reform of pesantren in Sidosermo, Surabaya, in integrating traditional values ​​with the modern education system. The research method used is a mixed methods method with an exploratory approach. Qualitative data were obtained through in-depth interviews, participant observation, and document studies, while quantitative data were collected through surveys and analyzed using statistical regression. The results showed that teaching methods had the most significant influence on the level of pesantren adaptation (β = 3.906), followed by teacher qualifications (β = 3.740) and facilities and infrastructure (β = 1.581). The support of ulama played a major role in pesantren reform (Sig. = 0.007), although in some cases it can be an obstacle if it is not in line with modernization policies. The conclusion of this study is that pesantren reform must be carried out gradually with an inclusive approach, involving all stakeholders so that it can be widely accepted without eliminating the identity of the pesantren. This study is expected to contribute to the development of sustainable pesantren education policies in the modern era.